Imagining mobility: the prospective cognition question in migration research. - Koikkalainen, Saara; Kyle, David (Journal of Ethnic & Migration Studies, 2016)
Most migration research is focused on migrant experiences after mobility and settlement. We argue that empirical researchers would benefit from studying howcognitive migration, the narrative imagining of oneself inhabiting a foreign destination prior to the actual physical move, influences migration behaviour. This article notes a gap in our current understanding of theprocessby which individuals decide to cross international borders and offers an agenda for remedying this. The interdisciplinarity of migration research has not fully extended to social psychology or cognitive social sciences, where a dynamic research agenda has examined human decision-making processes, including prospection and the connections between culture and cognition. The study of socio-cognitive processes in migration decision-making has been largely overlooked because of the after-the-fact nature of data collection and analysis rather than an aversion to these approaches per se. We highlight a number of strategic findings from this diverse field, provide examples of migration scholarship that has benefited from these insights, and raise questions about the sides of migration process that have received insufficient attention. A more nuanced understanding of prospective thinking—imagining potential futures—can shed light on the classic puzzle of why some people move while others in comparable situations do not.